Evaluating the Impact of Providing Training for Direct Care Staff in how to Provide an Emotionally Nurturing Environment for People with Intellectual Disability and Complex Needs - Frankish, Pat (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
The service is providing supported living for a number of people, male and female, age 21 to 55, who all have intellectual disability and a range of extra needs. These include physical disability, communication difficulties, trauma related personality difficulties, self-harming behaviour and aggression towards others. They are all perceived to have emotional developmental needs, all having suffered traumatic experiences in early childhood, causing developmental delay. All have difficulties with relationships associated with attachment disorders. All direct support staff are trained in models of emotional development and how to assess the emotional level, which leads to identifying the needs. Managers of services are alto trained to support the staff to provide the level of support needed, and to understand the systemic effects of trauma so as to be able to provide trauma-informed-care. The training, supervision, support and individual therapy for clients, where needed, is provided by psychologists and psychotherapists trained in Disability Psychotherapy. The comprehensive approach allows people with very complex and distressed behaviour to live in ordinary housing in the community. Data is provided on 10 people, the history, the initial problem behaviour and the present position after being provided with the emotionally nurturing environment.